2013
DOI: 10.4018/ijcbpl.2013070103
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of High and Low Technologies on Emotional Support for Caregivers

Abstract: Understanding the role of modern technology in providing adjunctive emotional support to caregivers has been a focus in contemporary caregiving research. However, it remains largely unknown (1) whether there are differences regarding the technologies used in caregiving support to achieve this objective and (2) which factors influence the outcome of emotional support. The current research describes a framework to address this issue and examines the role of different technologies in supporting caregiver emotiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Internet‐ or telehealth‐based support can be delivered remotely, accessed at the caregiver's convenience, and potentially serve as an education repository for future learning. Zheng et al reported that electronic delivery can enhance older caregivers’ acquisition and recall of educational information, and these findings have been validated elsewhere . This study examined whether an electronic‐based intervention could be deployed in support of rural caregivers of veterans with dementia.…”
mentioning
confidence: 77%
“…Internet‐ or telehealth‐based support can be delivered remotely, accessed at the caregiver's convenience, and potentially serve as an education repository for future learning. Zheng et al reported that electronic delivery can enhance older caregivers’ acquisition and recall of educational information, and these findings have been validated elsewhere . This study examined whether an electronic‐based intervention could be deployed in support of rural caregivers of veterans with dementia.…”
mentioning
confidence: 77%
“…Although much research has been conducted to understand the impact of individual constructs on older adults' Internet use, there is a dearth in research to understand how older adults perceive these constructs in relation to Internet use (Zheng et al, 2013). Further, limited research has been done to understand how demographic and other variables such as computer experience, health and financial information needs, and life satisfaction would influence older adults' perceptions on Internet use.…”
Section: Examined Urban Elders' Older Adults' Perceptions Of Internetmentioning
confidence: 94%
“…O'Connor (2013) examined patterns of online behavior (e.g., information seeking and Internet use) of a group of U.S. retirees and found that health information and financial management topped the list in terms of quality of life and leisure needs. However, Hardt and Hollis-Sawyer (2007) pointed out that even though the Internet may be growing in popularity in terms of seeking health and financial information, it is still not the primary medium older adults use to find health and financial information, partly because of concerns about credibility and partly because of web design that fails to consider older adults' cognitive limitations when surfing the Internet (Zheng et al, 2013). Given the high needs of older adults in seeking health and financial information, the constructs of health and financial information were included in the study.…”
Section: Health and Financial Information Needsmentioning
confidence: 97%
“…Technology has considerable potential to support home care provision. A large body of research exists in human-computer interaction (HCI) to mainly support patients [4-7] but also caregivers [6,8-13] in the context of in-home care. Thus far, however, in developing technologies for caregivers, research has generally emphasized functional support for caregiving (how can a caregiver provide better, more effective care?…”
Section: Introductionmentioning
confidence: 99%